Tanggung Jawab KSEI Sebagai Lembaga Penyimpanan Dan Penyelesaian (LPP) dalam Bursa Efek Indonesia - Yuweni, Junita; Septiawanani, Rizka; Anisa, Rika (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study aims to find out and explain how KSEI's responsibility as a depository and settlement institution in the Indonesia stock exchange. The method that the author used in this study was to use a qualitative descriptive method with a literature view. The results of the study stated that the storage and settlement institutions according to Law Number 8 of 1995 concerning Capital Securities Article 1 number 10 reads